Euro area banks' market power, lending channel and stability: The effects of negative policy rates - Yener Altunbaðs; Giuseppe Avignone; Christoffer Kok Sørensen; Cosimo Pancaro (European Central Bank (ECB), 2023)
This paper investigates to what extent the introduction of negative monetary policy rates altered the competitive behaviour in the euro area banking sector. Specifically, it analyses the effect that negative policy rates had on euro area banks' market power in comparison to banks that have not been subject to negative rates. The analysis, considering a sample of 4,223 banks over the period 2011-2018 and relying on a difference-in-differences methodology, finds that negative monetary policy rates led to an increase in euro area banks' market power. Furthermore, it shows that, during the negative interest rate policy period, change in banks' competitive behaviour affected the bank lending channel and discouraged banks from taking excessive risks.
Keywords: 44; E52; E58; G20; G21; 330; NIRP; Lerner index; Bank lending channel; Bank Stability; DiD